Implementasi Asas Keadilan Dalam Penyusunan Peraturan Perundang-Undangan - Nabila Mauldy Erwanto; Eva Shifdlotul Gisna; Carlos Damero; Nabila Izzaba Fillard; Baihaqi Abdul Hakim; Kuswan Hadji (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
The principle of fairness is an important principle in various matters. In drafting legislation, it is necessary to require the principle of justice to create social welfare. In this paper we raise the formulation of problems related to the implementation of the principle of justice in drafting legislation and the urgency of the principle of justice in drafting legislation. The method we use is a normative research method with the aim of finding out the implementation of the principles of justice in statutory regulations as well as conducting library research by collecting data, previous journals and legal regulations which are used as material in this writing. Based on the implementation of the principle of justice in drafting laws and regulations, the principle of justice is very important and reflects various aspects that exist within the Indonesian state. The urgency of this principle of justice is that it can create social welfare without anything that conflicts with morals, ethics and culture in society so that society can accept these regulations if they have been ratified.